Adaptation of an existing measure to assess professionals' attitudes regarding the importance of involving fathers in interventions with families - Christine Gervais; Sophie Meunier; Francine deMontigny; Diane Dubeau (Réseau de recherche en interventions en sciences infirmières du Québec (RRISIQ), 2018)
Introduction. Despite greater father participation in child care/rearing nowadays and the challenge of involving fathers in nursing interventions, no instrument exists to measure professional attitudes toward father involvement in family interventions. Objectives. The aim of this study was to adapt an existing measure that assesses nurse attitudes regarding the importance of including families in nursing care into a measure that assesses professionals' attitudes towards the importance of involving fathers in interventions with families. Method. The Professionals' Attitudes towards Father Involvement (PAFI) scale was adapted from the Families' Importance in Nursing Care - Nurse Attitudes (FINC-NA) scale. A total of 297 professionals in family care completed the 26 items of the PAFI. Results. Items analysis indicated three items had low variability and abnormal distribution. Principal component analysis was conducted with the 23 remaining items. Results revealed a solution with four factors reproducing the structure of the original scale: Father as conversational partner, Father as resource, Father as burden, and Father as own resource. Most items loaded on their original factor. The four subscales and the global scale showed good internal consistency. Discussion and conclusion. Even though further studies are needed, this adapted scale now enables researchers and practitioners to assess professionals' attitudes towards the importance of involving fathers in interventions with families.